Benefits of early initiation of estrogen replacement therapy after surgical castration - Paszkowski, Tomasz; Woźniakowska, Ewa (Menopause Review/Przegląd Menopauzalny, 2006)
Surgical castration following bilateral oophprectomy performed in premenopausal women results in a rapid decrease in blood estrogen level leading to multidirectional negative health consequences. Early initiation of the estrogen replacement therapy (ERT) is widely recommended in cases of surgical menopause as it offers proven benefits in the postoperative period in both short-term and long-term perspectives. It is reasonable to start ERT early – soon after a patient has been mobilised. Transdermal route of administration of estrogens seems to be optimal in those patients. The starting dose should be relatively high (75-100 mcg E2/24h) and the gradual down-titration of a dose is recommended to reach the minimally effective one.